PELATIHAN KEWIRAUSAHAAN MELALUI USAHA KREATIF DAN INOVATIF MASYARAKAT DESA TEGAL SARI KECAMATAN MEGANG SAKTI KABUPATEN MUSI RAWAS - Agung Nugroho; Rusni Eka Putra; Ahmad Amin (LP4MK STKIP PGRI Lubuklinggau, 2018)
The purpose of the author to do this PKM is entrepreneurship training in making shredded oyster mushrooms and marketing them online in the village of Tegal Sari, Megang Sakti District, Musi Rawas Regency. The problem in this PKM is